Prevalence, prognostic value, pathophysiology, and management of hyponatraemia in children and adolescents with COVID-19 - Tzoulis, Ploutarchos (Acta Biomedica Atenei Parmensis, 2021)
Hyponatraemia is frequently encountered in adults with coronavirus disease 2019 (COVID-19) and is associated with poor prognosis. This review aims to describe for the first time the prevalence, aetiology, prognostic value, pathophysiology, and management of hyponatraemia in children and adolescents with COVID-19, taking into account all relevant studies published in PubMed and Cochrane Library studies until 26th September 2021. Literature search did not detect any studies evaluating the prevalence and prognostic value of sodium disorders in paediatric patients with COVID-19. A broader literature review showed a high prevalence of hyponatraemia in children with bacterial pneumonia, while some studies have reported that hyponatraemia is relatively common in Multisystem Inflammatory Syndrome in Children (MIS-C). In adults with COVID-19, an inverse association between sodium and interleukin-6 levels has been found, indicating that hyponatraemia could be used as a surrogate marker for the risk of cytokine storm and may facilitate the identification of patients who could benefit from immunomodulatory agents. Studies are urgently needed to evaluate the frequency and prognostic impact of electrolyte abnormalities in children with COVID-19. In the meantime, clinicians are urged to consider hyponatraemia in children with COVID-19 as a potential red flag, investigate the cause and administer fluids and other therapies accordingly.